2002
DOI: 10.1159/000065226
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference of Urinary Osmolality in German Children

Abstract: Background/Aims: Origin of sex difference in urinary osmolality. Methods: In 495 healthy children aged 4.0–14.9 years participating in the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) study (247 boys, 248 girls), the water intake recorded in 24-hour weighed dietary records along with urinary volume, osmolality and free water reserve in 24-hour urine samples from the same day as the dietary record were determined. Results: Boys showed a significantly higher energy intake, total water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 14 publications
6
24
1
2
Order By: Relevance
“…We observed the gender difference in IU Osm , with higher values in boys, a feature that was demonstrated in several industrialized countries before [18][19][20]. Across the study age spectrum, 24-h IU Osm presented weak positive association with age.…”
Section: Discussionmentioning
confidence: 50%
“…We observed the gender difference in IU Osm , with higher values in boys, a feature that was demonstrated in several industrialized countries before [18][19][20]. Across the study age spectrum, 24-h IU Osm presented weak positive association with age.…”
Section: Discussionmentioning
confidence: 50%
“…Higher urine osmolalities in males than females were also demonstrated in Germany (2.5-17.5 y-old: 801 vs 729 mosm/ kg, Robers & Manz, 1996;7.0-11.9 y-old 810 vs 706 mosm/ kg, Ebner & Manz, 2002; 50-76 y-old: 713 vs 610 mosm/kg, Singhof & Manz, 2001) and the UK (15-65 y-old: 749 vs 643 mosm/kg, Waters et al, 1967; 3-to 18-y-old: 896 vs 781 mosm/kg, Skinner et al, 1996). However, no significant sex difference was observed in Italy (3-month-to 12-y-old: 663 mosm/kg, Riva et al, 1984), Israel (2-to 6-y-old: 806 vs 760 mosm/kg, Phillip et al, 1993) and Poland (402 vs 380 mosm/kg, Fydryk J, personal communication).…”
Section: Gendermentioning
confidence: 82%
“…Montenegro-Bethancourt (2013) provided, for the first time, evidence for an association between fruit and vegetables intake and children hydration status. Although other authors (26,27) speculated that fruit and vegetables were an essential predictor of hydration status, we also assessed the association with other food groups such as "milk and dairy products", and "coffee, barley, sodas, juices and water". Nonetheless, our findings revealed that only high "fruit and vegetables" intake was significantly associated with a better hydration status.…”
Section: Discussionmentioning
confidence: 99%